Photopolymer system based on fluorine-containing liquid crystal, grating device and preparation method of grating device

By using the mixing of fluorine-containing liquid crystals and nematic liquid crystals in the photopolymer system, the problem that photopolymer systems in the prior art are difficult to achieve high diffraction efficiency and low haze at the same time, and better optical performance and stability are achieved.

CN119569944AActive Publication Date: 2025-03-07NIKA OPTICS (TIANJIN) CO LTD

Patent Information

Application Number
CN202510138594.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing photopolymer system based on holographic polymer dispersed liquid crystals is difficult to achieve high diffraction efficiency and low haze at the same time when preparing holographic waveguide AR lenses. It is usually necessary to increase the material thickness or liquid crystal usage, resulting in an increase in haze.

Method used

A photopolymer system based on fluorine-containing liquid crystal is adopted. By adding fluorine-containing liquid crystal monomers to the nematic liquid crystal, the ratio of use is adjusted to improve the polarity and dielectric anisotropy of the liquid crystal, thereby improving the uniformity and thermal stability of the photopolymer system.

Benefits of technology

It achieves the haze of the grating device while maintaining high diffraction efficiency and has excellent optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_10
    Figure SMS_10
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

According to the photopolymer system based on the fluorine-containing liquid crystal, the grating device and the preparation method of the grating device, the mixed liquid crystal containing the nematic liquid crystal and the fluorine-containing liquid crystal at the same time is adopted in the photopolymer system, and therefore the polarity and dielectric anisotropy of the mixed liquid crystal material are improved; the overall electro-optical performance, uniformity and stability of the photopolymer system are improved, so that a grating device prepared based on the photopolymer system has good optical characteristics of low haze while having relatively high diffraction efficiency. Specifically, fluorine-containing biphenyl liquid crystals, fluorine-containing alkyne liquid crystals and fluorine-containing difluoromethoxy liquid crystals of which the carbon atoms of flexible side chains are 2-5, and nematic liquid crystals of which the delta epsilon is not less than 10 are selected to jointly form mixed liquid crystals; and the balance and optimization between the diffraction efficiency and haze performance of the photopolymer system and the grating device prepared from the photopolymer system are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of holographic projection display, and more specifically, to a photopolymer system based on fluorine-containing liquid crystal, a grating device and a preparation method thereof. Background Art

[0002] Holographic display technology is a technology that uses the principles of interference and diffraction to record and reproduce the optical information of three-dimensional objects. It can not only present a three-dimensional image of an object, but also show the color, texture and dynamic changes of the object, thus bringing a new visual experience to display technology. The core of holographic display technology lies in the production of holograms. Holograms are made by irradiating lasers onto objects and using the principles of interference and diffraction to record the optical information of the object. Subsequently, this optical information can be reproduced as a three-dimensional image, allowing users to observe different sides of the object from different angles. Based on different implementation methods, holographic display technology can be used to produce various types of holograms, such as reflective, transmissive and color holograms.

[0003] Holographic Polymer Dispersed Liquid Crystal (H-PDLC) grating is the product of the combination of holographic technology and polymer dispersed liquid crystal. It is a structured optoelectronic information material and device formed by the periodic arrangement of a polymer-rich phase and a liquid crystal-rich phase. It has the characteristics of high efficiency, switchability, excellent processing performance, and excellent optical performance. It is widely used in high-tech fields such as holographic storage, display, tunable filter, modulated laser, augmented reality (AR), etc. The preparation principle is to mix the monomer, liquid crystal and photoinitiator evenly and then pour them into a liquid crystal box with a fixed box thickness, and then perform photopolymerization under the action of laser coherence. In the bright area of ​​the laser coherent stripe, the free radicals generated by the photoinitiator absorbing photons initiate the polymerization of the monomers. The change in the chemical potential of the system causes the polymer and the liquid crystal to separate, prompting the liquid crystal molecules to diffuse from the bright area of ​​the coherent stripe to the dark area. At the same time, the monomers in the dark area diffuse to the bright area of ​​the coherent stripe for further polymerization, thereby forming a grating structure with periodic distribution of components and refractive index. The photopolymer system based on polymer-dispersed liquid crystal formed above has the characteristics of being able to control the polymerization reaction and adjust the arrangement state of liquid crystal molecules by light, and can also adjust the dispersion of liquid crystal molecules by controlling the degree of polymerization of the polymer matrix, thereby adjusting the optical properties of the system; at the same time, after the photopolymer system is cured, the polymer matrix provides good mechanical strength and chemical stability, and has high long-term stability, so it has wide application advantages in the fields of display, modulator, optical switch, etc.

[0004] However, there are still some challenges in using the photopolymer system based on holographic polymer dispersed liquid crystal in the field of holographic display. For example, when preparing holographic waveguide AR lenses, since the requirements for haze and efficiency of holographic waveguide AR lenses are relatively high, and the existing gratings prepared by the photopolymer system based on holographic polymer dispersed liquid crystal are usually dealt with by increasing the material thickness or increasing the amount of liquid crystal used to improve the diffraction efficiency. Increasing the material thickness can increase the thickness of the grating to increase the path length of the phase change, thereby enhancing the diffraction ability of the grating, but at the same time it will cause the volume of the material to increase, thereby introducing more light scattering, resulting in increased haze. When the refractive index and diffraction efficiency of the grating are adjusted by adding liquid crystal, due to the large refractive index difference of the liquid crystal molecules, it may cause uneven refractive index distribution in the polymer substrate, thereby increasing light scattering and causing increased haze. Therefore, it is necessary to provide a new photopolymer system based on holographic polymer dispersed liquid crystal and a grating device with low haze and high diffraction efficiency prepared by the system for use in AR glasses waveguide lenses. Summary of the invention

[0005] The present invention aims to overcome at least one defect of the above-mentioned prior art and provides a photopolymer system based on fluorine-containing liquid crystal and a grating device thereof, thereby improving the uniformity and thermal stability of the photopolymer system, thereby maintaining low haze while maintaining high diffraction efficiency of the grating device prepared by the photopolymer system, and having excellent optical properties.

[0006] The technical solution adopted by the present invention is first to provide a photopolymer system based on fluorine-containing liquid crystals, characterized in that it includes: Solvent: 5-10 parts, Mixed liquid crystal: 5-25 parts, Photoinitiator: 0.5-2 parts, Co-initiator: 2-6 parts, First monomer: 5-15 parts, Second monomer: 5-15 parts, The third monomer: 10-20 parts; The first monomer, the second monomer, and the third monomer are acrylate monomers having different functionalities; The mixed liquid crystal includes 70%-95% nematic liquid crystal and 5%-30% fluorine-containing liquid crystal; The Δε of the nematic liquid crystal is not less than 10; Wherein, the fluorine-containing liquid crystal has the following structural formula: , , , , , , , , ; Wherein, Rn (n is an integer from 1 to 16) is -F or -H, Mi (i is an integer from 1 to 2) is -F or an alkyl group having 2 to 5 carbon atoms; and at least one group in Rn or Mi is -F.

[0007] In the present technical solution, a mixed liquid crystal is used in the provided photopolymer system. By adding fluorine-containing liquid crystal monomers to nematic liquid crystals, the types and mixing ratios of the fluorine-containing liquid crystal monomers and the nematic liquid crystal monomers are adjusted to achieve a balance and optimization between the performances, thereby improving the polarity and dielectric anisotropy of the mixed liquid crystal material, thereby improving the overall electro-optical performance, uniformity and stability of the photopolymer system, so that the grating device prepared based on this photopolymer system has good optical properties of low haze while having high diffraction efficiency. Specifically, the fluorine-containing liquid crystals used are fluorine-containing biphenyl liquid crystals, fluorine-containing acetylene liquid crystals and fluorine-containing difluoromethoxy liquid crystals, in which the fluorine atoms can increase the dipole moment, increase the polarity of the liquid crystal molecules in the mixed liquid crystal, and further enhance the interaction between the molecules, thereby improving the dielectric anisotropy (i.e., Δε) of the mixed liquid crystal material, thereby improving the overall polarity of the mixed liquid crystal. Furthermore, since the fluorinated biphenyl liquid crystal molecules also have a polyaromatic ring structure, due to the strong conjugation, it is more conducive to improving the birefringence of the mixed liquid crystal and reducing the moment of inertia, thereby reducing the overall viscosity of the mixed liquid crystal, improving the fluidity of the mixed liquid crystal in the photopolymer system, thereby improving the uniformity of the liquid crystal distribution in the photopolymer system, thereby reducing the haze of the grating device prepared based on this photopolymer system; and the fluorinated difluoromethoxy liquid crystal has a difluoromethoxy group, so that the mixed liquid crystal has a larger molecular polarity while maintaining a low viscosity, thereby enhancing the dielectric anisotropy of the mixed liquid crystal in the photopolymer system and enhancing the optical modulation effect of the mixed liquid crystal, thereby reducing the haze of the grating device prepared based on this photopolymer system while improving the diffraction efficiency. Further, since the viscosity of the liquid crystal increases with the increase of the carbon atoms in the flexible side chain, in order to ensure the low viscosity performance of the fluorinated liquid crystal while ensuring the length of the liquid crystal molecule and thus ensuring the normal use performance of the liquid crystal, the carbon atoms of the flexible side chain of the fluorinated liquid crystal molecule used are selected to be controlled to be 2 to 5. Furthermore, in order to match the fluorine-containing liquid crystal monomer used and achieve a balance and optimization between the diffraction efficiency and the haze performance, preferably, the Δε of the selected nematic liquid crystal is not less than 10, thereby improving the overall dielectric anisotropy of the mixed liquid crystal and enhancing the optical modulation effect of the mixed liquid crystal, thereby reducing the haze of the grating device prepared based on this photopolymer system while improving the diffraction efficiency.

[0008] Furthermore, due to the addition of high-polarity fluorine-containing liquid crystals to the mixed liquid crystals, the compatibility of the entire mixed liquid crystal system becomes better, thereby reducing the haze of the system. Because the fluorine-containing liquid crystals will reduce the viscosity of the mixed crystals, the gel time will be longer during subsequent exposure, the grating regularity will be improved, and the diffraction efficiency will also be improved. If the amount of fluorine-containing liquid crystal is too low, the material compatibility may be insufficient. If the amount is too much, the performance of the mixed liquid crystal will be changed, which may cause the grating morphology formed subsequently to change. Therefore, the mixed liquid crystal is controlled to include 70%-95% nematic liquid crystals and 5%-30% fluorine-containing liquid crystals, thereby ensuring the optimization effect of the mixed liquid crystal while improving the processing convenience. At the same time, an unsaturated monomer system is formed by combining three acrylate monomers with different functionalities. The polymerization degree and crosslinking rigidity between the unsaturated monomers in the photopolymer system are improved through the crosslinking synergistic effect between the three unsaturated monomers. By adjusting the type and proportion of the added unsaturated monomers, the efficiency of the polymerization reaction between the monomers in the mixed liquid crystal adjustment system can be coordinated, and at the same time, the diffraction efficiency, haze and thermal stability of the prepared holographic grating device can be specifically adjusted and improved.

[0009] Preferably, in order to achieve a balance and optimization between the overall diffraction efficiency and haze performance of the photopolymer system, the diffraction efficiency is improved while the haze of the grating device prepared based on the photopolymer system is reduced; preferably, in order to achieve performance matching between mixed liquid crystals, thereby improving the overall dielectric anisotropy of the mixed liquid crystals and enhancing the optical modulation effect of the mixed liquid crystals, the fluorine-containing liquid crystals are selected from one or more of ethyl p-fluorotolane, 4-ethyl-2,6-difluoro-4'-(4-propylphenyl)-tolane, propyl-3,4-difluorotolane, pentyl p-fluorobiphenyl, propylphenyl-2',3,4,5-tetrafluorobiphenyl, and p-propyl-2,6-difluorobiphenyl-difluoromethoxy-3,4,5-trifluorobenzene; the nematic liquid crystal is E7. Further preferably, in order to match the performance of the above-mentioned mixed liquid crystal and at the same time specifically adjust and improve the diffraction efficiency, haze and thermal stability of the prepared holographic grating device, the types of the three unsaturated monomers added are selected accordingly. Specifically, the first monomer is a monofunctional monomer selected from one or more of isobornyl methacrylate, isodecyl methacrylate, 2-phenoxyethyl methacrylate, cyclohexyl methacrylate, lauric acid methacrylate, dicyclopentane methacrylate, and benzyl methacrylate; the second monomer is a difunctional monomer selected from one or more of ethylene glycol dimethacrylate, 4 (ethoxy) bisphenol A dimethacrylate, 1,3-butanediol dimethacrylate, and triethylene glycol dimethacrylate; the third monomer is one or more of trimethylolpropane triacrylate with trifunctionality or pentaerythritol tetraacrylate with tetrafunctionality. In the technical solution, the diffraction efficiency, uniformity, and thermal stability of the photopolymer system are improved by the combined use of mixed liquid crystals and unsaturated monomers, while the haze of the system is reduced, so that the grating device prepared by the photopolymer system has better comprehensive performance and service life. At the same time, the unsaturated monomers contained in the photopolymer system can be selected and combined from polymer monomers with different functionalities, and the selection is diverse, and the source of raw materials is wide and easy to obtain. While ensuring the function of the holographic grating device, the production convenience is improved and the production cost is reduced.

[0010] Furthermore, the photoinitiator is selected from one or more of photoinitiator 184, TPO, 3,3'-carbonylbis(7-diethylaminocoumarin), Rose Bengal, methylene blue, rhodamine 6G, and diiodofluorescein.

[0011] Furthermore, the co-initiator is selected from one or more of N-phenylglycine and benzoyl peroxide.

[0012] Furthermore, the solvent is selected from one or more of N-vinyl pyrrolidone, chloroform, tetrahydrofuran and toluene.

[0013] The technical solution also provides a method for preparing a grating device, wherein the grating device is prepared by using the photopolymer system described in the technical solution, and the method for preparing the grating device comprises the following steps: S1. adding the fluorine-containing liquid crystal to the nematic liquid crystal, and mixing by ultrasonication at 80-120° C. for 20-40 min to form the mixed liquid crystal; S2. The photopolymer system containing the mixed liquid crystal prepared in step S1 is mixed and poured into a liquid crystal box, which is placed still in a dark room, and then interference exposed under the interference light field of a double-beam light source.

[0014] Optionally, the interference exposure time is 1-5 min, the irradiation power is 4-6 mW / cm2; and the angle between the dual-beam light sources is 35°-60°.

[0015] Optionally, the thickness of the liquid crystal box is 4-6 μm.

[0016] Furthermore, in the step S2, the mixing step is: placing the photopolymer system containing the mixed liquid crystal prepared in step S1 in an ultrasonic instrument and mixing it evenly at 60° C. for 20-40 minutes to obtain a photopolymer mixed liquid; filling the photopolymer mixed liquid into a liquid crystal box under a vacuum atmosphere, and standing it in a dark room for 1-2 hours.

[0017] The technical solution also provides a grating device, which is prepared by the preparation method described in the technical solution.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. By using a mixed liquid crystal containing both nematic liquid crystal and fluorine-containing liquid crystal in the provided photopolymer system, and by adjusting the types and mixing ratios of the fluorine-containing liquid crystal monomer and the nematic liquid crystal monomer to achieve a balance and optimization of performance, the polarity and dielectric anisotropy of the mixed liquid crystal material are improved, thereby improving the overall electro-optical performance, uniformity and stability of the photopolymer system, so that the grating device prepared based on the photopolymer system has good optical properties of low haze while having high diffraction efficiency.

[0019] 2. The fluorine-containing liquid crystal used is a fluorine-containing biphenyl liquid crystal, a fluorine-containing acetylene liquid crystal or a fluorine-containing difluoromethoxy liquid crystal, wherein the fluorine atoms can increase the dipole moment, thereby increasing the polarity of the liquid crystal molecules in the mixed liquid crystal, thereby enhancing the interaction between the molecules, and thus being able to improve the dielectric anisotropy of the mixed liquid crystal material, thereby improving the overall polarity of the mixed liquid crystal and improving the diffraction efficiency of the photopolymer system. At the same time, since the fluorinated biphenyl liquid crystal molecules also have a polyaromatic ring structure, due to the strong conjugation, it is more conducive to improving the birefringence of the mixed liquid crystal and reducing the moment of inertia, thereby reducing the overall viscosity of the mixed liquid crystal, improving the fluidity of the mixed liquid crystal in the photopolymer system, thereby improving the uniformity of the liquid crystal distribution in the photopolymer system, thereby reducing the haze based on the photopolymer system; and the fluorinated difluoromethoxy liquid crystal contains a difluoromethoxy group, which makes the mixed liquid crystal have a larger molecular polarity while maintaining a lower viscosity, thereby enhancing the dielectric anisotropy of the mixed liquid crystal in the photopolymer system and enhancing the optical modulation effect of the mixed liquid crystal, thereby reducing the haze of the grating device prepared based on the photopolymer system while improving the diffraction efficiency.

[0020] 3. By selecting nematic liquid crystals with a Δε of not less than 10, the nematic liquid crystals in the mixed liquid crystals are matched with the fluorinated liquid crystals, thereby improving the dielectric anisotropy of the mixed liquid crystals as a whole, enhancing the optical modulation effect of the mixed liquid crystals, and achieving a balance and optimization between the diffraction efficiency and haze performance of the photopolymer system. At the same time, due to the addition of high-polarity fluorinated liquid crystals to the mixed liquid crystals, the compatibility of the entire mixed liquid crystal system becomes better, thereby reducing the haze of the system, because the fluorinated liquid crystals will reduce the viscosity of the mixed crystals, the gel time will be longer during subsequent exposure, the grating regularity will be improved, and the diffraction efficiency will also be improved. By controlling the mixed liquid crystals to include 70%-95% nematic liquid crystals and 5%-30% fluorinated liquid crystals, the optimization effect of the mixed liquid crystals is ensured while the processing convenience is improved.

[0021] 4. In the provided photopolymer system, an unsaturated monomer system is formed by selecting a combination of three acrylate monomers with different functionalities. The type and proportion of the added unsaturated monomers are adjusted and the cross-linking synergistic effect between the three unsaturated monomers is used to improve the polymerization degree and cross-linking rigidity between the unsaturated monomers in the photopolymer system. The efficiency of the polymerization reaction between the monomers in the mixed liquid crystal adjustment system is coordinated to specifically adjust and optimize the diffraction efficiency, haze, thermal stability and other properties of the prepared holographic grating device. DETAILED DESCRIPTION

[0022] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0023] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0024] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not specified in the examples, they are usually carried out according to conventional conditions or according to the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels).

[0025] In the present invention, a mixed liquid crystal system formed by mixing fluorine-containing liquid crystal and nematic liquid crystal is adopted. Since the fluorine-containing liquid crystal molecules have a strong dipole moment and a unique electronic structure, the response of the liquid crystal molecules in the electric field can be enhanced by their polarity, and the polarization effect of the liquid crystal molecules under the action of the electric field is enhanced by the electron attraction effect of the fluorine atoms, thereby improving the Δε of the mixed liquid crystal; at the same time, due to the strong electron negativity of the fluorine atoms, the intermolecular force of the liquid crystal molecules is weak, and the fluorine-containing liquid crystal molecules usually have a lower viscosity. Adding a certain amount of fluorine-containing liquid crystal to the nematic liquid crystal helps to improve the fluidity of the liquid crystal, thereby improving the electro-optical response performance of the photopolymer system in various device applications. Furthermore, the strong bonding between fluorine atoms and carbon atoms (such as CF bonds) makes fluorine-containing liquid crystal molecules more resistant to high temperatures than ordinary liquid crystal molecules, and makes fluorine-containing liquid crystal molecules have better thermal stability. At the same time, the low polarity and strong electron negativity of the fluorine element will make the thermal expansion coefficient of the fluorine-containing liquid crystal lower, thereby reducing the dimensional change of the liquid crystal material under thermal load. Introducing fluorine-containing liquid crystal monomers into nematic liquid crystals can improve the stability of the mixed liquid crystal material at higher temperatures, thereby broadening the operating temperature range of the mixed liquid crystal material, thereby improving the performance of the photopolymer system in various device applications.

[0026] Example 1 This embodiment provides a photopolymer system based on fluorine-containing liquid crystal, a grating device and a preparation method thereof, specifically comprising the following steps: (1) Preparation of photopolymer system: S1. Add 4.5 parts of ethyl parafluorotolane to 10.5 parts of E7, mix under ultrasonication at 80-120°C for 20-40 minutes to form a mixed liquid crystal, and then test the dielectric constant of the mixed liquid crystal; wherein Δε of E7 is 11.4 or 13.8; S2. Weigh the following raw materials from a brown sample bottle: 0.5 parts of 3,3'-carbonylbis(7-diethylaminocoumarin), 2 parts of N-phenylglycine, 10 parts of 2-phenoxyethyl methacrylate, 15 parts of 4(ethoxy)bisphenol A dimethacrylate, 10 parts of trimethylolpropane triacrylate, and 7 parts of N-vinyl pyrrolidone; The weighed raw materials and the mixed liquid crystal prepared in step S1 are placed in an ultrasonic instrument for 30 minutes for uniform mixing to obtain a uniformly mixed photopolymer system; then, the viscosity of the photopolymer system at 25° C. is measured according to GB / T22235-2008 DIN53229 “Determination of Viscosity of Liquids”.

[0027] (2) Preparation of grating devices: The photopolymer system was filled into a liquid crystal box under vacuum conditions. The liquid crystal box had a thickness of 5 μm. After filling, the liquid crystal box was moved to a dark room and left to stand for 1 hour. Then, the system was moved to a dark room with an angle of 60° and an irradiation power of 5 mW / cm 2 The grating device is finally obtained by interference exposure in the interference light field of the double-beam light source for 5 minutes.

[0028] (3) Diffraction efficiency test: The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic grating device by using a grating diffraction efficiency tester.

[0029] (4) Haze test: The specific steps of the haze test are: using a haze meter to test the haze of the obtained holographic grating device at 23±2°C according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics".

[0030] Example 2 This embodiment provides a photopolymer system based on fluorine-containing liquid crystal, a grating device and a preparation method thereof, specifically comprising the following steps: (1) Preparation of photopolymer system: S1. Add 1.3 parts of amyl-p-fluorobiphenyl to 23.8 parts of E7, mix under ultrasonication at 80-120° C. for 20-40 min to form a mixed liquid crystal, and then test the dielectric constant of the mixed liquid crystal; wherein Δε of E7 is 11.4 or 13.8; S2. Weigh the following raw materials from a brown sample bottle: 2 parts of photoinitiator 184, 6 parts of benzoyl peroxide, 15 parts of isobornyl methacrylate, 10 parts of ethylene glycol dimethacrylate, 15 parts of pentaerythritol tetraacrylate, and 5 parts of chloroform; The weighed raw materials and the mixed liquid crystal prepared in step S1 are placed in an ultrasonic instrument for 30 minutes for uniform mixing to obtain a uniformly mixed photopolymer system; then, the viscosity of the photopolymer system at 25° C. is measured according to GB / T22235-2008 DIN53229 “Determination of Viscosity of Liquids”.

[0031] (2) Preparation of grating devices: The photopolymer system was filled into a liquid crystal box under vacuum conditions. The liquid crystal box had a thickness of 5 μm. After filling, the liquid crystal box was moved to a dark room and left to stand for 1 hour. Then, the system was moved to a dark room with an angle of 60° and an irradiation power of 5 mW / cm 2 The grating device is finally obtained by interference exposure in the interference light field of the double-beam light source for 5 minutes.

[0032] (3) Diffraction efficiency test: The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic grating device by using a grating diffraction efficiency tester.

[0033] (4) Haze test: The specific steps of the haze test are: using a haze meter to test the haze of the obtained holographic grating device at 23±2°C according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics".

[0034] Example 3 This embodiment provides a photopolymer system based on fluorine-containing liquid crystal, a grating device and a preparation method thereof, specifically comprising the following steps: (1) Preparation of photopolymer system: S1. Add 4.5 parts of amyl-p-fluorobiphenyl to 20.5 parts of E7, mix under ultrasonication at 80-120° C. for 20-40 min to form a mixed liquid crystal, and then test the dielectric constant of the mixed liquid crystal; wherein Δε of E7 is 11.4 or 13.8; S2. Weigh the following raw materials from a brown sample bottle: 1 part TPO, 4 parts N-phenylglycine, 12 parts benzyl methacrylate, 13 parts 1,3-butanediol dimethacrylate, 20 parts pentaerythritol tetraacrylate, and 10 parts toluene; The weighed raw materials and the mixed liquid crystal prepared in step S1 are placed in an ultrasonic instrument for 30 minutes for uniform mixing to obtain a uniformly mixed photopolymer system; then, the viscosity of the photopolymer system at 25° C. is measured according to GB / T22235-2008 DIN53229 “Determination of Viscosity of Liquids”.

[0035] (2) Preparation of grating devices: The photopolymer system was filled into a liquid crystal box under vacuum conditions. The liquid crystal box had a thickness of 5 μm. After filling, the liquid crystal box was moved to a dark room and left to stand for 1 hour. Then, the system was moved to a dark room with an angle of 60° and an irradiation power of 5 mW / cm 2 The grating device is finally obtained by interference exposure in the interference light field of the double-beam light source for 5 minutes.

[0036] (3) Diffraction efficiency test: The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic grating device by using a grating diffraction efficiency tester.

[0037] (4) Haze test: The specific steps of the haze test are: using a haze meter to test the haze of the obtained holographic grating device at 23±2°C according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics".

[0038] Comparative Example 1 This comparative example provides a photopolymer system, a grating device and a preparation method thereof, specifically comprising the following steps: (1) Preparation of photopolymer system: Weigh the following raw materials from the brown sample bottle: 0.5 parts of 3,3'-carbonylbis(7-diethylaminocoumarin), 2 parts of N-phenylglycine, 10 parts of 2-phenoxyethyl methacrylate, 15 parts of 4(ethoxy)bisphenol A dimethacrylate, 10 parts of trimethylolpropane triacrylate, 7 parts of N-vinylpyrrolidone, 15 parts of E7; wherein the Δε of E7 is 11.4; The weighed raw materials are placed in an ultrasonic instrument for 30 minutes to be mixed evenly to obtain a uniformly mixed photopolymer system; then, the viscosity of the photopolymer system at 25° C. is measured according to GB / T22235-2008 DIN53229 “Determination of Viscosity of Liquids”.

[0039] (2) Preparation of grating devices: The photopolymer system was filled into a liquid crystal box under vacuum conditions. The liquid crystal box had a thickness of 5 μm. After filling, the liquid crystal box was moved to a dark room and left to stand for 1 hour. Then, the system was moved to a dark room with an angle of 60° and an irradiation power of 5 mW / cm2 The grating device is finally obtained by interference exposure in the interference light field of the double-beam light source for 5 minutes.

[0040] (3) Diffraction efficiency test: The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic grating device by using a grating diffraction efficiency tester.

[0041] (4) Haze test: The specific steps of the haze test are: using a haze meter to test the haze of the obtained holographic grating device at 23±2°C according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics".

[0042] Comparative Example 2 This embodiment provides a photopolymer system based on fluorine-containing liquid crystal, a grating device and a preparation method thereof, specifically comprising the following steps: (1) Preparation of photopolymer system: S1. Add 4.5 parts of 4,7-dibromo-5,6-difluoro-benzothiadiazole to 10.5 parts of E7, mix under ultrasonication at 80-120° C. for 20-40 min to form a mixed liquid crystal, and then test the dielectric constant of the mixed liquid crystal; wherein Δε of E7 is 11.4 or 13.8; S2. Weigh the following raw materials from a brown sample bottle: 0.5 parts of 3,3'-carbonylbis(7-diethylaminocoumarin), 2 parts of N-phenylglycine, 10 parts of 2-phenoxyethyl methacrylate, 15 parts of 4(ethoxy)bisphenol A dimethacrylate, 10 parts of trimethylolpropane triacrylate, and 7 parts of N-vinyl pyrrolidone; The weighed raw materials and the mixed liquid crystal prepared in step S1 are placed in an ultrasonic instrument for 30 minutes for uniform mixing to obtain a uniformly mixed photopolymer system; then, the viscosity of the photopolymer system at 25° C. is measured according to GB / T22235-2008 DIN53229 “Determination of Viscosity of Liquids”.

[0043] (2) Preparation of grating devices: The photopolymer system was filled into a liquid crystal box under vacuum conditions. The liquid crystal box had a thickness of 5 μm. After filling, the liquid crystal box was moved to a dark room and left to stand for 1 hour. Then, the system was moved to a dark room with an angle of 60° and an irradiation power of 5 mW / cm 2 The grating device is finally obtained by interference exposure in the interference light field of the double-beam light source for 5 minutes.

[0044] (3) Diffraction efficiency test: The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic grating device by using a grating diffraction efficiency tester.

[0045] (4) Haze test: The specific steps of the haze test are: using a haze meter to test the haze of the obtained holographic grating device at 23±2°C according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics".

[0046] Comparative Example 3 This embodiment provides a photopolymer system based on fluorine-containing liquid crystal, a grating device and a preparation method thereof, specifically comprising the following steps: (1) Preparation of photopolymer system: S1. Add 4.5 parts of ethyl parafluorotolane to 10.5 parts of E7, mix under ultrasonication at 80-120°C for 20-40 minutes to form a mixed liquid crystal, and then test the dielectric constant of the mixed liquid crystal; wherein Δε of E7 is 11.4 or 13.8; S2. Weigh the following raw materials from a brown sample bottle: 0.5 parts of 3,3'-carbonylbis(7-diethylaminocoumarin), 2 parts of N-phenylglycine, 10 parts of o-phenylphenoxyethyl acrylate, 15 parts of 4(ethoxy)bisphenol A dimethacrylate, 10 parts of trimethylolpropane triacrylate, and 7 parts of N-vinyl pyrrolidone; The weighed raw materials and the mixed liquid crystal prepared in step S1 are placed in an ultrasonic instrument for 30 minutes for uniform mixing to obtain a uniformly mixed photopolymer system; then, the viscosity of the photopolymer system at 25° C. is measured according to GB / T22235-2008 DIN53229 “Determination of Viscosity of Liquids”.

[0047] (2) Preparation of grating devices: The photopolymer system was filled into a liquid crystal box under vacuum conditions. The liquid crystal box had a thickness of 5 μm. After filling, the liquid crystal box was moved to a dark room and left to stand for 1 hour. Then, the system was moved to a dark room with an angle of 60° and an irradiation power of 5 mW / cm 2 The grating device is finally obtained by interference exposure in the interference light field of the double-beam light source for 5 minutes.

[0048] (3) Diffraction efficiency test: The specific steps of the diffraction efficiency test are: testing the diffraction efficiency of the above-mentioned holographic grating device by using a grating diffraction efficiency tester.

[0049] (4) Haze test: The specific steps of the haze test are: using a haze meter to test the haze of the obtained holographic grating device at 23±2°C according to GB 2410-2008 "Test method for light transmittance and haze of transparent plastics".

[0050] In Example 1 to Example 3, the photopolymer system is set to select and combine the components and formulas provided in the technical solution. While using the mixed liquid crystal material containing fluorine-containing liquid crystal and nematic liquid crystal as provided by the present invention, the first monomer, the second monomer and the third monomer with different functionalities provided by the present invention are selected to form an unsaturated monomer system. Specifically, the fluorine-containing liquid crystal is selected from ethyl p-fluorotolane, 4-ethyl-2,6-difluoro-4'-(4-propylphenyl)-tolane, propyl-3,4-difluorotolane, pentyl p-fluorobiphenyl, propylphenyl-2',3,4,5-tetrafluorobiphenyl, p-propyl-2,6-difluorobiphenyl-difluoromethoxy -3,4,5-trifluorobenzene; nematic liquid crystal adopts E7; the first monomer is a monofunctional monomer, selected from one or more of isobornyl methacrylate, isodecyl methacrylate, 2-phenoxyethyl methacrylate, cyclohexyl methacrylate, lauric acid methacrylate, dicyclopentyl methacrylate; the second monomer is a difunctional monomer, selected from ethylene glycol dimethacrylate, 4 (ethoxy) bisphenol A dimethacrylate, 1,3-butanediol dimethacrylate, triethylene glycol dimethacrylate; the third monomer is one or more of trimethylolpropane triacrylate with trifunctionality or pentaerythritol tetraacrylate with tetrafunctionality. By using a mixed liquid crystal containing both nematic liquid crystal and fluorine-containing liquid crystal in the formed photopolymer system, and by adjusting the types and mixing ratios of the fluorine-containing liquid crystal monomer and the nematic liquid crystal monomer to achieve balance and optimization of performance, the polarity and dielectric anisotropy of the mixed liquid crystal material are improved, thereby improving the overall electro-optical performance, uniformity and stability of the photopolymer system, so that the grating device prepared based on the photopolymer system has good optical properties of low haze while having high diffraction efficiency; at the same time, by selecting three acrylate monomers with different functionalities to form an unsaturated monomer system, by adjusting the types and ratios of the added unsaturated monomers and by the cross-linking synergistic effect of the three unsaturated monomers, the polymerization degree and cross-linking rigidity between the unsaturated monomers in the photopolymer system are improved, thereby coordinating with the mixed liquid crystal to adjust the efficiency of the polymerization reaction between the monomers in the system, and specifically adjusting and optimizing the diffraction efficiency, haze and thermal stability of the prepared holographic grating device.

[0051] In the photopolymer system provided in Comparative Example 1, fluorine-containing liquid crystal is not included, and at least one type of polymer monomer among the selected first monomer, second monomer or third monomer is selected from other monomers that do not belong to the selection range of the first monomer, second monomer and third monomer provided in the present technical solution; in the photopolymer system provided in Comparative Example 2, the type of fluorine-containing liquid crystal provided by the present invention is not used, and at least one type of polymer monomer among the selected first monomer, second monomer or third monomer is selected from other monomers that do not belong to the selection range of the first monomer, second monomer and third monomer provided in the present technical solution; in the photopolymer system provided in Comparative Example 3, the type of fluorine-containing liquid crystal provided by the present invention is used, and at least one type of polymer monomer among the selected first monomer, second monomer or third monomer is selected from other monomers that do not belong to the selection range of the first monomer, second monomer and third monomer provided in the present technical solution.

[0052] The six photopolymer systems and grating devices prepared therefrom in Examples 1 to 3 and Comparative Examples 1 to 3, the dielectric constant of the liquid crystal used in the photopolymer system, the viscosity of the photopolymer system as a whole, the diffraction efficiency and haze results of the grating device are shown in the following table:

[0053] By comparing Examples 1-3 with Comparative Example 1, it can be found that the results of the liquid crystal dielectric constant and viscosity of the obtained photopolymer system, as well as the diffraction efficiency and haze of the grating device prepared therefrom show that: in the photopolymer system, adding a mixed liquid crystal containing a certain proportion of fluorine-containing liquid crystal can increase the liquid crystal dielectric constant of the mixed liquid crystal and reduce the overall viscosity of the photopolymer system, thereby improving the overall electro-optical performance, uniformity and stability of the photopolymer system, so that the grating device prepared based on this photopolymer system has good optical properties with higher diffraction efficiency and lower haze.

[0054] By comparing Examples 1-3 and Comparative Examples 1-3, it can be found that there is a certain cross-linking synergistic effect between the mixed liquid crystal and the polymer monomers used in the photopolymer system. By adopting the types and proportions of fluorine-containing liquid crystals and nematic liquid crystals as in the present invention, combined with the types and proportions of the three unsaturated monomers as in the present invention, the mixed liquid crystal system and the unsaturated monomers can be cross-linked and coordinated with each other, so that the grating device prepared therefrom has higher diffraction efficiency, lower haze, and better optical effect.

[0055] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A photopolymer system based on fluorinated liquid crystals, characterized in that: include: Solvent: 5-10 parts, Mixed liquid crystal: 5-25 parts, Photoinitiator: 0.5-2 parts, Co-initiator: 2-6 parts, First monomer: 5-15 parts, Second monomer: 5-15 parts, The third monomer: 10-20 parts; The first monomer, the second monomer, and the third monomer are acrylate monomers having different functionalities; The mixed liquid crystal includes 70%-95% nematic liquid crystal and 5%-30% fluorine-containing liquid crystal; The Δε of the nematic liquid crystal is not less than 10; The fluorine-containing liquid crystal has the following structural formula: , , , , , , , , , wherein Rn (n is an integer from 1 to 16) is -F or -H, Mi (i is an integer from 1 to 2) is -F or an alkyl group having 2 to 5 carbon atoms; and at least one R1 to R4 or M is -F.

2. The photopolymer system according to claim 1, characterized in that The fluorine-containing liquid crystal is selected from one or more of ethyl p-fluorotolane, 4-ethyl-2,6-difluoro-4'-(4-propylphenyl)-tolane, propyl-3,4-difluorotolane, pentyl p-fluorobiphenyl, propylphenyl-2',3,4,5-tetrafluorobiphenyl, p-propyl-2,6-difluorobiphenyl-difluoromethoxy-3,4,5-trifluorobenzene; The nematic liquid crystal is E7; The first monomer is selected from one or more of isobornyl methacrylate, isodecyl methacrylate, 2-phenoxyethyl methacrylate, cyclohexyl methacrylate, lauric acid methacrylate, and dicyclopentyl methacrylate; The second monomer is selected from ethylene glycol dimethacrylate, 4 (ethoxy) bisphenol A dimethacrylate, 1,3-butanediol dimethacrylate, triethylene glycol dimethacrylate; The third monomer is selected from one or more of trimethylolpropane triacrylate and pentaerythritol tetraacrylate.

3. The photopolymer system according to claim 1, characterized in that The photoinitiator is selected from one or more of photoinitiator 184, TPO, 3,3'-carbonylbis(7-diethylaminocoumarin), rose Bengal, methylene blue, rhodamine 6G, and diiodofluorescein.

4. The photopolymer system according to claim 1, characterized in that The co-initiator is selected from one or more of N-phenylglycine and benzoyl peroxide.

5. The photopolymer system according to claim 1, characterized in that The solvent is selected from one or more of N-vinyl pyrrolidone, chloroform, tetrahydrofuran and toluene.

6. A method for preparing a grating device, characterized in that: The grating device is prepared by using the photopolymer system according to any one of claims 1 to 5, and the preparation method of the grating device comprises the following steps: S1. adding the fluorine-containing liquid crystal to the nematic liquid crystal, and mixing by ultrasonication at 80-120° C. for 20-40 min to form the mixed liquid crystal; S2. The photopolymer system containing the mixed liquid crystal prepared in step S1 is mixed and poured into a liquid crystal box, which is placed still in a dark room, and then interference exposed under the interference light field of a double-beam light source.

7. The preparation method according to claim 6, characterized in that: The interference exposure time is 1-5 minutes, and the irradiation power is 4-6 mW / cm 2 ; and the angle between the dual-beam light sources is 35°-60°.

8. The preparation method according to claim 6, characterized in that: The thickness of the liquid crystal cell is 4-6 μm.

9. The preparation method according to claim 6, characterized in that: In the step S2, the mixing step is: placing the photopolymer system containing the mixed liquid crystal prepared in step S1 in an ultrasonic instrument and mixing it evenly at 60° C. for 20-40 minutes to obtain a photopolymer mixed liquid; filling the photopolymer mixed liquid into a liquid crystal box under a vacuum atmosphere, and leaving it to stand in a dark room for 1-2 hours.

10. A grating device, characterized in that: Prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Holographic polymer dispersed liquid crystal material and application thereof

    CN117431072A

  • Anti-aging holographic polymer dispersed liquid crystal composition, grating device and preparation method

    CN118421331A

  • Low-haze holographic polymer dispersed liquid crystal composition, grating device and preparation method

    CN118440706A

  • Anti-aging holographic polymer dispersed liquid crystal material, grating device and preparation method of grating device

    CN118894962A

  • Holographic polymer dispersed liquid crystal material, grating device and preparation method thereof

    CN118894972A

Cited By

  • Holographic polymer dispersed liquid crystal composition, holographic grating and preparation method

    CN121135955A

  • Holographic polymer dispersed liquid crystal composition, holographic grating and method of preparation

    CN121135955B